The effect of various types of forest fires on pine resin productivity in Gunung Walat University Forest, Sukabumi, Indonesia - CHRISTINE DELLA PRASETYA; LAILAN SYAUFINA; GUNAWAN SANTOSA (Biodiversitas Journal of Biological Diversity, 2017)
Prasetya CD, Syaufina L, Santosa G. 2017. The effect of various types of forest fires on pine resin productivity in Gunung Walat University Forest, Sukabumi, Indonesia. Biodiversitas 18: 476-482. Gunung Walat University Forest (GWUF) of Sukabumi, Indonesia is one of pine resin producers that has 71 hectares of resin production area. The forest fire burned 7 hectares of resin production area in August 2015 was expected to affect the resin productivity. The aim of this study was to analyze the effect of each type of forest fire to pine resin productivity and analyze the correlation between the biophysic aspect and pine resin productivity after the fire. The types of forest fire were litter and shrub fire, stem fire, and crown fire. ANOVA test showed that the types of forest fire have significant effect to resin production with the value of Ftable (3.12)<Ftest (4.88) and Pvalue (0.006)<? (0.05). The Tukey test showed that the stem fire and the crown fire gave the most significant result to the resin production with the mean of resin productivity value (g/tree/day) respectively 24.54 and 21.698.